2020
DOI: 10.1002/etc.4730
|View full text |Cite
|
Sign up to set email alerts
|

Metal Element Detection and Carcinogenicity Risk Assessment of PM2.5 Samples

Abstract: The objective of the present study was to conduct metal element analysis and carcinogenicity risk assessment of particulate matter with an aerodynamic diameter <2.5 μm (PM2.5) from Shenzhen and Taiyuan. Samples of PM2.5 were collected in Shenzhen and Taiyuan during the yeas 2017 and 2018. Ten heavy metal elements were detected by inductively coupled plasma mass spectrometry. Health risk was assessed using the recommended US Environmental Protection Agency model. Metal elements found in PM2.5 samples from Shenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Cu, Zn, V, and Ni were the most abundant metals for nearly all cities. Coal processing is one of the potential sources of the metals in PM 2.5 as reported by Qin, et al 55 V and Ni are mainly released from the petrochemical oil refinery in Malaysia. 25,26 Cu is potentially emitted from the brake wears as the brake pad consists of Cu, as reported by Pant.…”
Section: Resultsmentioning
confidence: 99%
“…Cu, Zn, V, and Ni were the most abundant metals for nearly all cities. Coal processing is one of the potential sources of the metals in PM 2.5 as reported by Qin, et al 55 V and Ni are mainly released from the petrochemical oil refinery in Malaysia. 25,26 Cu is potentially emitted from the brake wears as the brake pad consists of Cu, as reported by Pant.…”
Section: Resultsmentioning
confidence: 99%
“… 1 , 2 Several epidemiological studies have shown that long-term exposure to high levels of PM2.5 increases the risk of many respiratory diseases, such as influenza, 3 , 4 asthma, 5 bronchitis, 6 chronic obstructive pulmonary disease (COPD), 7 , 8 pulmonary fibrosis, 9 and lung cancer. 10 , 11 As a result, PM2.5-induced lung injury poses an enormous social and economic burden. 12 , 13 Currently, respiratory diseases caused by PM2.5 have attracted widespread attention from scholars.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the relationship between the dynamic changes in the V/Ni ratio and the impact of ship sources on air quality in inland and coastal sites [30]. Before the implementation of DECA 2.0, the V/Ni ratio in particulate matter in coastal cities such as Shanghai (more than 1.0) and Qingdao (more than 0.7) were higher than those of Zhengzhou (0.34), Xinxiang (0.22) and Taiyuan (0.43), Chengdu (0.41), and other inland cities [31,[34][35][36]. However, current research needs more reports on the proportion of metal trace elements in the follow-up policy of DECA 2.0.…”
Section: Introductionmentioning
confidence: 99%